Keterkaitan Pengetahuan Dan Perencanaan Keuangan Terhadap Perilaku Karyawan Pria - Hendra Wiyanto; Yohana Ika Putri; Herlina Budiono (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2019)
This study aims to analyze and find out the relationship between financial knowledge and financial planning on the financial behaviour of male employees with fixed income who live in Jakarta with a minimum of S1 education. This study uses primary data in the form of a questionnaire totalling 76 respondents. The program used in this study is SMART-PLS version 3.2.7 using the Structural Equation Modeling (SEM) model. The results of this study are that there is no significant influence between financial knowledge on the financial behaviour of male employees and there is a positive and significant effectbetween financial planning on the financial behaviour of male employees.